Using Multi-Criteria Decision Models in Investigating the Key Factors of Success in Marketing and Location Branding in an Uncertain Environment - Ghasem Farajpour Khanaposhti (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: In today's business environment, marketing and brand management are critical. Studies show that business owners' high and attractive skill is known by their ability to create and manage a brand. For this reason, brands are one of the most important visible assets of the organization. One of the prominent examples of marketing is location marketing. In this type of marketing, the goal is to create a brand identity in a specific geographic location. Key success factors must be identified for successful location marketing and branding. There are several key factors for location marketing and branding success. This research aims to identify and evaluate the impact of each of these key success factors.Methodology: The research experts selected five key success factors. The statistical population of this research was considered the reputable marketing and branding consulting companies of the country, and finally, 35 questionnaires were examined. This research used the fuzzy hierarchical analysis method to rank the five key success factors.Findings: The results showed that "strategic vision and analysis" and "planning groups" impact location marketing and branding success most among the five factors.Originality/Value: The present research addresses location marketing, branding, and the key success factors in marketing.